2019
DOI: 10.1159/000497287
|View full text |Cite
|
Sign up to set email alerts
|

Emicizumab in the Treatment of Acquired Haemophilia: A Case Report

Abstract: The prognosis of acquired haemophilia A (AHA) is severe and treatment options are limited. Emicizumab is a novel bispecific humanized monoclonal antibody in the treatment of inherited AHA with inhibitors. An 83-year-old AHA patient with congestive heart failure and a high risk for thromboembolic and cardiac events who had initially been treated successfully with steroids and substitution of recombinant B-domain-deleted porcine FVIII developed severe bleeding complications and a secondary increase in inhibitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 9 publications
0
44
0
2
Order By: Relevance
“…56 The drug has been used in a few patients with AHA with severe bleeding. 57,58 However, the safety and efficacy of emicizumab in AHA is unknown and so this antibody should not be used in this group of patients outside of clinical trials. This is particularly relevant for elderly patients, in whom cardiovascular events are more common, and in women who are considering use of hormonal therapy or future pregnancy, as emicizumab is an IgG4 antibody and may therefore be transferred across the placenta.…”
Section: Anti-fibrinolytics and Other Treatmentsmentioning
confidence: 99%
“…56 The drug has been used in a few patients with AHA with severe bleeding. 57,58 However, the safety and efficacy of emicizumab in AHA is unknown and so this antibody should not be used in this group of patients outside of clinical trials. This is particularly relevant for elderly patients, in whom cardiovascular events are more common, and in women who are considering use of hormonal therapy or future pregnancy, as emicizumab is an IgG4 antibody and may therefore be transferred across the placenta.…”
Section: Anti-fibrinolytics and Other Treatmentsmentioning
confidence: 99%
“…More recently, the clinical benefits of emicizumab have been documented in some AHA patients with unresolved severe bleeding. [19][20][21][22] These reports also recorded a fatality, however, in one patient treated with emicizumab on compassionate grounds. 22 The current clinical trials of emicizumab have not included patients with AHA, however, and reliable evidence-based data on the potential use of this therapy in AHA is warranted.…”
Section: Introductionmentioning
confidence: 95%
“…Pathophysiological concepts and studies using a primate monkey model of AHA have suggested that emicizumab might be useful for the hemostatic management of AHA as well as congenital HA. More recently, the clinical benefits of emicizumab have been documented in some AHA patients with unresolved severe bleeding . These reports also recorded a fatality, however, in one patient treated with emicizumab on compassionate grounds .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations